PENGEMBANGAN BAHAN AJAR SEJARAH LOKAL BERBASIS NILAI-NILAI SULAM KERAWANG GAYO UNTUK MENINGKATKAN KARAKTER BANGSA SISWA KELAS XI SMA NEGERI DI KABUPATEN BENER MERIAH - Iswanto, Sufandi; W., Warto; D., Djono (Sebelas Maret University (UNS), 2015)
This research aim to find: (1) the analyze how conditions of teaching materials history; (2).the described of the development local history of teaching materials based on values of The Embroidery Kerawang Gayo to improve nation character of the students, and (3) the description of the effectiveness local history of teaching materials based on values The Embroidery Kerawang Gayo in improving the nation character students.Research method development (Research and Development / R&D) of borg and gall was used in this research to produce teaching materials. Stage methods are: (1) the preliminary stage of the study, namely the study of literature, field studies, needs and findings of teaching materials; (2) the developmental stage, includes: design prototypes, validation expert’ s judgement, the trial and the revision of one-on-one, and piloting broad; (3) And the test of the effectiveness stage, includes: test the effectiveness and appropriation teaching materials local history. The results obtained: (1) the teaching materials referring to KTSP, focused on one text book without any partners and also the development of teaching materials, regarding school facilities in the history of teaching materials are not enough, less of giving materials about character education, and teachers are too pursue time to resolve the matter, so that needs of teaching materials with an emphasis on the nation character; (2) teaching materials local history is based on six components determined, the syllabus and lesson plans, validation of three experts give the value of the average score category 5 with very good, one by one the trial conducted in 5 students and 13 students with the value of the average score 4.4 with the category of very good, the revision of which are only the format of the writing, the results of the trial wide showed that there are differences in between average value of the experiment more increase than both control group of achievement and the attitude of the nation character; and (3) the application of teaching materials local history based on values kerawang gayo embroidery in order to increase nation character has proved effective, proven by the value of post group test on control and the experiment group, to yield achievement of 0.005 < 0.025 and attitude nation character of 0.005 < 0.025 by this Ho rejected so there is a difference of positive and significant.